Decree Law of the President of the Arab Republic of Egypt No. 160/2013 On Amending Some Provisions of the Traffic Law Promulgated by Law No. 66/1973 = قرار رئيس جمهورية مصر العربية بالقانون رقم 160 لسنة 2013 في شأن تعديل بعض أحكام قانون المرور الصادر بالقانون رقم 66 لسنة 1973 / presidency - Egypt. presidency (2025)
Decree Law of the President of the Arab Republic of Egypt No. 160/2013 On Amending Some Provisions of the Traffic Law Promulgated by Law No. 66/1973 قرار رئيس جمهورية مصر العربية بالقانون رقم 160 لسنة 2013 في شأن تعديل بعض أحكام قانون المرور الصادر بالقانون رقم 66 لسنة 1973